Професійна підготовка бакалаврів гуманітарних наук з політології в університетах Англії та Уельсу - Брандибура, Ірина Юріївна (Національний університет "Львівська політехніка", 2019)
У дисертаційній роботі запропоновано вирішення наукового завдання щодо виявлення особливостей професійної підготовки бакалаврів гуманітарних наук з політології в умовах університетської освіти Англії та Уельсу (автономізація, інтернаціоналізація і персоналізації освітнього процесу; диверсифікація освітніх програм; міждисциплінарний характер освітніх програм; гнучкість змісту освітніх програм; прикладний характер освітніх програм; акцентуація на самостійній та науково-дослідній роботі в освітньому процесі; широке використання методів активного навчання та інформаційно-комунікаційних технологій; забезпечення академічної мобільності здобувачів вищої освіти; інтегрованість системи професійної підготовки бакалаврів політології у міжнародний освітньо-науковий простір; забезпечення контролю якості вищої освіти); висвітлено професійну підготовку бакалаврів гуманітарних наук з політології як науково-педагогічну проблему, в основу якої покладено теорії, концепції, принципи, підходи філософії, політології, соціології, педагогіки, психології, економіки; досліджено організаційно-педагогічні засади професійної підготовки бакалаврів гуманітарних наук з політології в університетах Англії та Уельсу на основі розробленої структурної моделі, що охоплює нормативно-правовий, теоретико-методологічний, цільовий, стимулювально-мотиваційний, змістовий, операційний, контрольно-регулювальний та оцінно-результативний компоненти; на основі порівняльно-педагогічного аналізу виокремлено спільне та відмінне у досвіді Англії, Уельсу й України; розроблено науково-методичні рекомендації щодо використання прогресивного досвіду Англії та Уельсу у системі університетської освіти України. Уточнено зміст понять «бакалавр гуманітарних наук з політології», «фахівець з політології». Подальшого розвитку набули положення про організацію професійної підготовки майбутніх фахівців з політології на основі комплексного використання традиційних та інноваційних методів навчання із застосуванням інформаційно-комунікаційних технологій, тісної співпраці університетів з місцевою громадою і потенційними роботодавцями. В диссертационной работе предложено решение научной задачи по выявлению особенностей профессиональной подготовки бакалавров гуманитарных наук по политологии в условиях университетского образования Англии и Уэльса (автономизация, интернационализация и персонализации образовательного процесса; диверсификация образовательных программ; междисциплинарный характер образовательных программ; гибкость содержания образовательных программ; прикладной характер образовательных программ; акцентуация на самостоятельной и научно-исследовательской работе в образовательном процессе; широкое использование методов активного обучения и информационно-коммуникационных технологий; обеспечение академической мобильности соискателей высшего образования; интегрированность системы профессиональной подготовки бакалавров политологии в международное образовательно-научное пространство; обеспечение контроля качества высшего образования); представлено профессиональную подготовку бакалавров гуманитарных наук по политологии как научно-педагогическую проблему, в основу решения которой положены теории, концепции, принципы, подходы философии, политологии, социологии, педагогики, психологии, экономики; исследованы организационно-педагогические основы профессиональной подготовки бакалавров гуманитарных наук по политологии в университетах Англии и Уэльса на основе разработанной структурной модели, охватывающей нормативно-правовой, теоретико-методологический, целевой, стимулирующе-мотивационный, содержательный, операционный, контрольно-регулировочный и оценочно-результативный компоненты; на основе сравнительно-педагогического анализа выделено общее и отличное в опыте Англии, Уэльса и Украины; очерчено возможности использования прогрессивного опыта Англии и Уэльса в системе университетского образования Украины. Уточнено содержание понятий «бакалавр гуманитарных наук по политологии», «специалист по политологии». Дальнейшее развитие получили положения об организации профессиональной подготовки будущих специалистов по политологии на основе комплексного использования традиционных и инновационных методов обучения с применением информационно-коммуникационных технологий, тесного сотрудничества университетов с местной общиной и потенциальными работодателями. The thesis presents the solution to the research problem of identifying specificity of professional training of Bachelors of Arts in Political Science at the universities of England and Wales (autonomy, internationalization and personalization of educational process; diversification of educational programmes; multi- and interdisciplinary nature of educational programmes; flexibility of the content of educational programmes; applied character of educational programmes; focus on independent and research work in educational process; extensive use of active learning methods and information technologies; student academic mobility; integration of undergraduate political science education into international educational and research space; effective higher education quality assurance); professional training of Bachelors of Arts in Political Science has been presented a research problem, solving of which is based on complex integration of theories, concepts, principles, approaches of philosophy, sociology, pedagogy, psychology, economics; organizational and pedagogical principles of professional training of Bachelors of Arts in Political Science at the universities of England and Wales have been analyzed based on the components of the developed structural model (legal framework, theory and methodology, aim, motivation, content, operation, control and regulation, and assessment); common (modernization of the existing system of professional training of political scientists based on current international and national tendencies and priorities of higher education development; autonomy of universities; theoretical and methodological basis of professional training of Bachelors of Arts in Political Science; standardization of professional training; division of educational programmes into compulsory and optional components; application of competency-based approach to the development and implementation of undergraduate political science programmes) and distinctive (specific attributes of the experience of England and Wales are: high level of integration into international educational and research space; diversification of educational programmes through exploitation of multi- and interdisciplinary potential of political science; effective internationalization of education in terms of joint degrees; flexibility of educational programmes and students’ freedom in forming their own educational trajectory due to the ratio of compulsory and optional components; applied and analytical-research character of undergraduate political science programmes; variety of placement learning models; variety of research training models; promotion and support of undergraduate political science research as extracurricular activities; effective implementation of models of incorporation of teachers' research work into the process of preparation of Bachelors of Arts in Political Science; allocation of a considerable amount of political science student’s academic load to independent work; effective application of student-centered approach; active use of information technologies; collaboration of universities with potential employers to implement joint projects and to facilitate graduate employment; specific attributes of Ukraine's experience are: low degree of integration into international educational and research space; initial stage of exploitation of multi- and interdisciplinary approach to the development and implementation of undergraduate political science programmes; initial stage of internationalization of professional training; lack of flexibility and personalization of educational programmes in terms of ratio of compulsory and optional components; theoretical nature of training programs for Bachelors of Arts in Political Science; realization of short-term placement learning models; insufficiently systemic and thorough formation of research competence; insufficient efficiency of implementation of models of incorporation of teachers' research into the process of training Bachelors of Arts in Political Science; significant amount of classes and insufficient use of the potential of student independent work; insufficient application of student-centered approach; insufficient use of modern technologies; large academic load of undergraduate political science students in terms of credit numbers and number of hours per one credit) features of the researched countries have been identified; recommendations on creative use of progressive ideas of the English and Welsh experience of professional training of Bachelors of Arts in Political Science at Ukrainian universities have been developed. The notions "Bachelor of Arts in Political Science", "political science specialist" have been clarified. The ideas of organization of professional training of political scientists based on the comprehensive use of traditional and innovative teaching and learning methods combined with the use of information technologies, close collaboration of universities with local community and prospective employers have gained further development.
Профессиональная подготовка бакалавров гуманитарных наук по политологии в университетах Англии и Уэльса
Professional training of bachelors of arts in political science at the universities of England and Wales
Keywords: бакалавр гуманітарних наук; освітньо-професійна програма; політологія; професійна підготовка; університет; Англія; Уельс; бакалавр гуманитарных наук; образовательно-профессиональная программа; политология; профессиональная подготовка; университет; Англия; Уэльс; Bachelor of Arts; educational programme; political science; professional training; university; England; Wales; 378.4:32(410.1)